SISTEM INFORMASI GEOGRAFIS POPULASI TERNAK MENURUT KABUPATEN/KOTADAN JENIS TERNAK DI PROVINSI JAWA TENGAH PADA TAHUN 2022 - Puji Ratna Sari; Bambang Agus Herlambang, Ahmad Khoirul Anam (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Geographic Information System (GIS) plays a key role in managing livestock population data and planning the development of the livestock sector. In Central Java Province, the implementation of GIS-Livestock Population (GIS-LivPop) has successfully mapped the number of livestock populations based on geographical location, district/city, and livestock type in 2022. Through GIS technology, GIS-LivPop facilitates the mapping of the distribution of cattle, goats, sheep, chickens, and other livestock in the Central Java region. This data is animportant source of information for planning, monitoring livestock diseases, supplying animalfeed, and developing the livestock economy.